Information Engineering Course Management in Faculty of Engineering, KMITL towards excellence - Punyaruethai Purahong; Tuanjai Archevapanich; Vasutorn Chaowalittawin; Donnaporn Punthang; Gregory P. Millerteacher; Paisan Sithiyopasakul; Boonchana Purahong (My University, 2021)
This article represents the management of Information Engineering course in faculty of Engineering, KMITL towards excellence. Sample group is the parental units of who registered since 2017 until 2020 for 15 people, by purposive sampling. The researcher later presenting the Information Engineering course management. Then make a parental satisfaction assessment form about the Information Engineering course management in faculty of Engineering, King Mongkut's Institute of Technology Ladkrabang, towards excellence of 7 subject. The conclude of assessment says that the parental units are having a good level of satisfaction and the arithmetic mean is 4.72 and the standard deviation is 0.56 ( $\overline{X}$ =4.27, S.D. = 0.56)
Keywords: Innovative Teaching Methods; STEM Education; Technology-Enhanced Education Studies